Pathogenetic rationale for prescribing menopausal hormone therapy for systemic sclerosis - T. S. Panevin; L. P. Ananyeva (Научно-практическая ревматология, 2022)
Systemic scleroderma (SS) is characterized by dysregulation of the innate and adaptive immune systems, vasculopathy, and generalized fibrosis. As with most autoimmune diseases, women predominate among patients, who get sick 3–14 times more often than men. It is assumed that gender differences and modulation of sex hormones are essential in the pathogenesis of SS. Estrogens are able to influence the immune response, have a vasodilating effect and stimulate the synthesis of collagen in the skin. The development of SS leads to a significant decrease in the quality of life, psychological disorders associated with changes in appearance, as well as the need for lifelong medication with the frequent development of side effects. Age-related estrogen deficiency associated with the onset of menopause is accompanied by a decrease in the quality of life and, in some cases, a change in the clinical manifestations of somatic diseases. This review considers the impact of menopause and menopausal hormone therapy (MHT) on the course and clinical manifestations of systemic scleroderma. It is noted that SS in some cases is accompanied by an early onset of menopause. The use of MHT is not associated with the progression of cutaneous fibrosis, and may also improve the vascular manifestations of SS.